Das Märchen der Brüder Grimm „Die Bremer Stadtmusikanten“ unter musiktherapeutischen Aspekten - Wolfram, Ilse (eBooki.com.pl, 2014)
So far, the musictherapeutical relevance of the fairy tale „The Bremen Town Musicians“ has not yet been examined. In most cases, depending on the intentions of public and political players, the accent is being laid on jobless people, on marketing purposes of the city of Bremen, on the protection of animals, and so on. As this tale is of wide international range, the article cites questions and answers among Polish students of education, realized by Prof. Dr. Wita Szulcz, art therapist and lecturer in Educational Science. The musictherapeutical relevance explains itself through the expression of “making music together”, which guarantees the survival of the animal figures and which is at the same time the main feature in Music Therapy of all schools. After describing the general features in fairy tales as there are the symbols of location, of time, of numbers, the repetitions, of the plot itself, the author refers to the wellknown animals threatened by dead of four modes, as to refugees with individual personalities. In order to make musictherapeutic processes comprehensible, the author describes excerpts from a group music therapy with refugees, who found their experiences mirrored in this tale of the Bremen Town Musicians.
Keywords: Brothers Grimm; The Bremen Town Musicians; Poetic power; fleeing animals; Fleeing people; Fairy Tale; Let’s go to Bremen